2014
DOI: 10.1016/j.margen.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and activity of marine bacterioplankton during a diatom bloom in the North Sea assessed by total RNA and pyrotag sequencing

Abstract: A recent investigation of bacterioplankton communities in the German Bight towards the end of a diatom-dominated spring phytoplankton bloom revealed pronounced successions of distinct bacterial clades. A combination of metagenomics and metaproteomics indicated that these clades had distinct substrate spectra and consumed different algal substrates. In this study we re-analyzed samples from the initial study by total community RNA (metatranscriptomics) and 16S rRNA gene amplicon sequencing. This complementary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 51 publications
10
64
0
1
Order By: Relevance
“…We noted that different OTUs within Flavobacteriaceae, including Polaribacter , and Rhodobacteraceae peaked at different points during the phytoplankton bloom. This suggests niche specialization by different taxa within these groups, perhaps corresponding to different stages in the successive degradation of phytoplankton-derived organic compounds (Teeling et al, 2012; Klindworth et al, 2014). Polaribacter occurred in a cluster with only one other OTU ( Figures 3 and 4 ), suggesting a strong competitive advantage for Polaribacter early in the bloom, in support of the hypothesized role of this taxon (Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We noted that different OTUs within Flavobacteriaceae, including Polaribacter , and Rhodobacteraceae peaked at different points during the phytoplankton bloom. This suggests niche specialization by different taxa within these groups, perhaps corresponding to different stages in the successive degradation of phytoplankton-derived organic compounds (Teeling et al, 2012; Klindworth et al, 2014). Polaribacter occurred in a cluster with only one other OTU ( Figures 3 and 4 ), suggesting a strong competitive advantage for Polaribacter early in the bloom, in support of the hypothesized role of this taxon (Williams et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A recent metagenomic study showed that submerged insoluble polysaccharides such as cellulose are colonized by biofilm-forming marine bacterial communities, of which the Bacteroidetes are a major group that harbors an extensive repertoire of genes encoding glycoside hydrolases (803). Marine Bacteroidetes may also harbor TonB-dependent transport systems that can be used for the uptake of polysaccharides (804).…”
Section: Marine Bacteroidetesmentioning
confidence: 99%
“…That observed in one region at a given time are the changes in the relative abundance of community members (Gibbons et al 2013). In addition to qualitative descriptions, studies have also addressed seasonal, interannual, and interseasonal variations (Hatosy et al 2013, Karl andChurch 2014), and considerable advances have been made in understanding the metabolic processes of the communities and their role in biogeochemical cycles (Hahnke et al 2013, Karl and Church 2014, Klindworth et al 2014, Logares et al 2014). …”
Section: Comunidades Microbianas Marinasmentioning
confidence: 99%
“…Más allá de una descripción cualitativa, los estudios han profundizado para determinar los niveles de fluctuación estacional, interanual e interestacional de estas comunidades (Hatosy et al 2013, Karl y Church 2014. Actualmente, se están realizando grandes avances en el conocimiento de los procesos metabólicos que desarrollan las comunidades y su papel en los ciclos biogeoquímicos (Hahnke et al 2013, Karl y Church 2014, Klindworth et al 2014, Logares et al 2014). …”
Section: S Rrnaunclassified